CERRAHPAŞA TIP FAKÜLTESİ AİLE HEKİMLİĞİ POLİKLİNİĞİNE BAŞVURAN HASTALARIN 3 YILLIK PROFİLİ - SÜT, Necdet; SİPAHİOĞLU, Fikret and ERTÜRK, Nurver Turfaner (Cerrahpaşa Medical Journal, 2014)
Background and Design.- 285 randomly selected patients referring to family medicine policlinic back from November 2003 were analyzed in terms of most frequent illnesses and their relation with age and gender. The frequencies and coincidences of illnesses as well as their relation with age and gender were detected in enrolled patients of whom 185 were females and 100 were males by using statistical methods like descriptive study, cluster analysis, correlation and factor analysis. Results.- There was no difference between the mean age of 2 groups. The most frequent disease in both gender was hypertension. In women, anemia, osteoporosis and rheumatic complaints were more common while in men upper respiratory tract infections and venous insufficiency were more frequent. The other diseases displayed a similar distribution in both gender. In women, gastrointestinal problems decreased with age whereas hypertension, osteoporosis, hypercholesterolemia and ischemic heart disease with arrythmias increased. In men, upper respiratory tract infections declined with aging while hypertension, prosthatic complaints, diabetes and ischemic heart disease with arrythmias showed an increase. Also, some diseases tended to occur together in both gender. Conclusion.- In this research, hypertension appeared to be the most common and public health threating disease in both men and woman.